The Influence of the Sport Education Learning Model, Sports Motivation, and Social Support on Students' Mental Health - Amalya Nadhira Hiesan; Reni Silviah (Siber Nusantara Review, 2025)
The influence of the sport education learning model, sports motivation, and social support on students' mental health is a scientific article with the aim of analyzing whether mental health has an influence on the sport education learning model, sports motivation and social support. Qualitative method with a phenomenological approach, the phenomenological approach emphasizes the description of the subject's life experience from the participant's own perspective (phenomenology as a social research method). The results of this article are: 1) Student mental health influences the sport education learning model, 2) Student mental health influences the learning model that motivates sports, 3) Student mental health influences the learning model that receives social support. Apart from these 3 exogenous variables that influence the endogenous variable of mental health, there are still many other factors including the quality of education, teacher competence, teacher leadership, training consistency.